PATTERNS OF MAIZE CONSUMPTION AND FOOD LOSS AMONG HOUSEHOLDS IN GUCHA SUB-COUNTY, KISII COUNTY, KENYA - Cheruiyot, Kiprono Elijah; Wanjiku , Grace Njeri Mwangi; Otieno, Michael Onyango Ouma (Ayden International Journal of Education and Social sciences, 2025)
Despite growing research, academic investment and intervention programming on food security at national and household level, countries are still facing enormous challenges in attaining food security. In Kenya, albeit plenty food produced at household level, it is paradoxical that most of these households persistently experience food insecurity. This is partly blamed on household foodresource handling procedures at consumption stage that leads to food loss and waste. One of the major perceived reasons for this is the sociocultural situation which influences food handling processes at consumption level leading to direct food loss and waste. This paper interrogates the relationship between household food consumption patterns and food loss and waste in Gucha SubCounty, Kisii County, Kenya. The paper is an extract from the study that focused on household foodresource handling procedures and food security in Gucha Sub-County. Mixed research technique was utilized in collecting data on food beliefs, and its effect on food loss, waste and eventual food security/insecurity. The study found that different households adopt different food distribution mechanisms, food preferences, dietary patterns, household food allocation. Understanding household arrangements, social behavior, and cultural contexts which influence decision making processes in relation to food consumption behaviour are important in effective foodresource handling processes. It is the recommendation of the study that consumer education campaigns should be increased to provide knowledge and awareness on appropriate food types, food preparation skills, meal planning, using leftovers and food discard behaviour. The study provides evidence that once people are aware of the value of their losses, then there is commitment to handle food-resources better